An Analysis of Marxist Feminism In Austen's Pride And Prejudice - Jill, Jill Lovely Mamahit; Liando, Nihta V. F; Kukus, Fridolin (Program Studi Pendidikan Bahasa Inggris, 2024)
This study aims to analyze the concept of Marxist Feminism in Austen’s Pride and Prejudice, the writer used descriptive qualitative method to analyze and collect data about the Marxist Feminism in Austen’s Pride and Prejudice. This study uses a Marxist Feminism theory. This Marxist feminist framework reveals how Austen critiques social class and gender influence in economic structures, showing how personal relationships in the novel are interwoven with economic transactions and societal expectations. This research highlights the systemic nature of women's economic dependence and the limitations imposed by capitalist norms. By analyzing Pride and Prejudice through this lens, this research not only deepens the understanding of Austen's work, but also contributes to feminist literary criticism and the ongoing discourse on the socio-economic dimensions of literature.